Efektifitas Advokasi Hukum Keluarga Islam dalam Penegakan Hukum Keluarga - Alfikri, Ahmad Zaky; Okta, Merlista Luthfadia; Al-Ghifari, Miftah Heta; Syamsiah, Syamsiah; Noveri, Irsadunas (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Islamic family law is a normative instrument that has a strategic position in maintaining social stability and household harmony in Muslim society. In the Indonesian context, the challenges of implementing family law are increasingly complex along with the increasing domestic conflicts and limited public access to fair and dignified dispute resolution mechanisms. Advocacy of Islamic family law is an alternative means of realizing substantive justice through a non-litigative approach based on the values ​​of maqāṣid al-sharī‘ah. This study aims to analyze the effectiveness of Islamic family law advocacy in enforcing family law and to identify factors that support and hinder its implementation. The method used is a qualitative approach with a descriptive-analytical library research technique. Data sources are obtained from normative documents, scientific journals, and previous research results that are relevant to the issue of family law advocacy. The results of the study show that family law advocacy based on sharia mediation and Islamic values ​​has been proven to be able to reduce conflict escalation and increase public legal literacy. However, its effectiveness is still hampered by the dominance of litigative approaches, weak professionalism of advocates, and suboptimal synergy between institutions. This study concludes that the effectiveness of Islamic family law advocacy is influenced by three main variables: the capacity of legal actors in understanding maqāṣid al-sharī‘ah, solid institutional integration, and the state policy's bias towards an inclusive and transformative advocacy system. Thus, the reformulation of contextual and collaborative advocacy strategies is urgent in building a just and civilized family law system.